Derivation of mouse embryonic stem cell lines from tyrosine hydroxylase reporter mice crossed with a human SNCA transgenic mouse model of Parkinson's disease - Margarita Chumarina (Stem Cell Research, 2017)
Mouse embryonic stem cell (mESC) lines were derived by crossing heterozygous transgenic (tg) mice expressing green fluorescent protein (GFP) under the control of the rat tyrosine hydroxylase (TH) promoter, with homozygous alpha-synuclein (aSYN) mice expressing human mutant SNCAA53T under the control of the mouse Prion promoter (MoPrP), or wildtype (WT) mice. The expression of GFP and human aSYN was validated by immunocytochemistry in midbrain neuron cultures upon differentiation of mESC lines using stromal cell-derived inducing activity. These mESC lines can help to study the impact of human aSYN expression in neurons and oligodendrocytes, and also trace GFP-expressing midbrain neurons.